Outcome of standard tabularized incised plate urethroplasty repair using dartos flap and tunica vaginalis flap in of hypospadias cases - Patel, Jiwan Lal; Chandrakar, Sandeep; Memon, M. Amin; Mishra, Basumitra (International Surgery Journal, 2018)
Background: Hypospadias, with prevalence of 1 per 300 live births, is a congenital malformation caused by incomplete fusion of urethral folds, in which the meatal orifice opens on the inferior surface of the penis. The commonest complication of hypospadias surgery is fistula formation which requires re-operation. Several techniques of providing vascularised soft tissue cover to neourethra have been described. They include de-epithelized skin, corpus spongiosum, dartos fascia and tunica vaginalis. The purpose of our study was to compare outcomes of standard tubularised incised plate urethroplasty (TIP) repair using dartos flap and TVF in of hypospadias cases. Methods: This study was carried out in the Department of Surgery (Paediatric Surgery Division) of Pt. JNM Medical College and associated Dr. BRAM Hospital, Raipur in patients diagnosed to had distal, mid penile and proximal penile type of hypospadias. The study was carried out during the period from February 2016 to September 2017. Total no of cases studied was 55. All admitted patients for primary Snodgrass repair were randomized into two groups by Simple Random method to avoid selection bias. Group A of 27 patients were prospectively selected for repair using TVF for soft tissue cover. Group B of 28 Patients, comparable in age and type of hypospadias, who underwent TIP repair using dartos flap as soft tissue cover. Descriptive statistics were employed to characterize the data. Results: Patients were from 1 year to 13 years of age at time of surgery for hypospadias. Mean age being 4.69+3.15. There was almost equal number of patients in both groups of flap. Both groups were comparable in terms of age and type of hypospadias. Overall, dartos flap group had significantly higher rate of urethrocutaneous fistula formation than tunica vaginalis flap. In TVF group only one patient (3.7%) developed skin necrosis while in Dartos group 5 patients (17.86%) developed skin necrosis. Both TVF group and Dartos group had one patient with residual torsion. Conclusions: In present study we have noted higher rate of fistula formation and skin necrosis in dartos flap group as compared to tunica vaginalis. Tunica vaginalis flap definitely have an edge over preputial dartos flap and we would recommend its use as waterproofing second layer in hypospadias cases.